2013
DOI: 10.1007/s00393-013-1146-5
|View full text |Cite
|
Sign up to set email alerts
|

Resistin in inflammatory and degenerative rheumatologic diseases

Abstract: Resistin levels were found to be higher in the serum and synovial fluid of RA patients than in those with OA. This may suggest a role for resistin in inflammatory rheumatologic diseases. The observed statistically significant correlation between synovial fluid resistin levels and RF, ACPA and Larsen score may suggest that high synovial fluid resistin levels can be considered a poor prognostic factor for RA progression. However, further studies employing a larger cohort of patients are needed to confirm the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 37 publications
0
15
0
1
Order By: Relevance
“…These findings, together with the observation that the intra-articular injection of resistin in the knee joints induces arthritis, sustain the involvement of resistin in RA pathogenesis [110]. Several reports have demonstrated that serum resistin levels are significantly higher in RA than in OA patients or healthy controls [111–113]. The increased serum levels of resistin correlated with markers of inflammation, such as CRP, ESR, IL-1Ra, and total leukocyte count [47, 114117], disease activity (DAS28), and joint destruction [112].…”
Section: Resistinmentioning
confidence: 74%
See 2 more Smart Citations
“…These findings, together with the observation that the intra-articular injection of resistin in the knee joints induces arthritis, sustain the involvement of resistin in RA pathogenesis [110]. Several reports have demonstrated that serum resistin levels are significantly higher in RA than in OA patients or healthy controls [111–113]. The increased serum levels of resistin correlated with markers of inflammation, such as CRP, ESR, IL-1Ra, and total leukocyte count [47, 114117], disease activity (DAS28), and joint destruction [112].…”
Section: Resistinmentioning
confidence: 74%
“…The increased serum levels of resistin correlated with markers of inflammation, such as CRP, ESR, IL-1Ra, and total leukocyte count [47, 114117], disease activity (DAS28), and joint destruction [112]. However, these results were not confirmed by other groups [111], and conflicting results were reported on the association between resistin and radiographic progression signs [27, 31, 100]. Recently, the anti-TNF- α therapy was reported to modulate resistin levels in RA patients [118, 119] (Table 1).…”
Section: Resistinmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, resistin levels are found to be higher in the serum and synovial fluid of RA patients than in those with osteoarthritis (OA). The observed statistically significant correlation between synovial fluid resistin levels and rheumatoid factor (RF), anti-citrufllinated protein/peptide autoantibody (ACPA) and Larsen score which further indicate that locally produced adipokines are closely implicated in synovial inflammation during the pathogenesis of RA 38 .…”
Section: Discussionmentioning
confidence: 89%
“…It acts as a pro-inflammatory factor that increases the production of inflammatory cytokines and elevates the expression of cell adhesion molecules. While its exact biologic functions are still being elucidated, higher resistin levels have been associated with chronic inflammatory diseases such as rheumatoid arthritis and inflammatory bowel disease, and resistin may play a role in the pathophysiology of atherosclerosis and endothelial cell injury [ 86 , 87 ].…”
Section: Introduction Of Adipocytokinesmentioning
confidence: 99%